2014
DOI: 10.1111/ejh.12239
|View full text |Cite
|
Sign up to set email alerts
|

Zoledronic acid in the management of bone disease as a consequence of multiple myeloma: a review

Abstract: Background: Multiple myeloma (MM) is a haematological cancer associated with organ damage, essentially bone damage. MM continues to be considered an incurable disease and requires significant therapeutic resources. Aim: This manuscript presents a literature review of the utility of zoledronic acid (zoledronate) in the management of bone disease in MM. Discussion: The clinical benefit of bisphosphonates in the prevention and treatment of bone disease in MM has been demonstrated in the last 10 years. A recent ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
20
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 34 publications
0
20
0
Order By: Relevance
“…MM progression and drug resistance depend on interactions with the local microenvironment; therapies that target the marrow microenvironment rather than the tumor cells directly, such as bisphosphonates, have proven to be effective in inhibiting tumor growth and osteolysis, suggesting that targeting of the marrow can be an effective therapeutic avenue to pursue. [5][6][7][8][9][10] In addition to osteoblasts (OBs) and OCs, other BM niche cells, including mesenchymal stem cells (MSCs), BM adipocytes, immune cells, and osteocytes, also likely affect MM progression. 7 BM cells exist in a dynamic, stress-sensing environment where they release soluble signaling molecules to communicate with one another; how these signals are processed by MM cells invading the BM niche remains a key area of investigation.…”
Section: Introductionmentioning
confidence: 99%
“…MM progression and drug resistance depend on interactions with the local microenvironment; therapies that target the marrow microenvironment rather than the tumor cells directly, such as bisphosphonates, have proven to be effective in inhibiting tumor growth and osteolysis, suggesting that targeting of the marrow can be an effective therapeutic avenue to pursue. [5][6][7][8][9][10] In addition to osteoblasts (OBs) and OCs, other BM niche cells, including mesenchymal stem cells (MSCs), BM adipocytes, immune cells, and osteocytes, also likely affect MM progression. 7 BM cells exist in a dynamic, stress-sensing environment where they release soluble signaling molecules to communicate with one another; how these signals are processed by MM cells invading the BM niche remains a key area of investigation.…”
Section: Introductionmentioning
confidence: 99%
“…Zoledronic acid (ZOL) is a third‐generation bisphosphonate, which can inhibit bone destruction in patients with metastatic bone tumors or multiple myeloma . Moreover, ZOL has been shown to exert an antitumor effect against osteosarcoma cells .…”
mentioning
confidence: 99%
“…Zoledronic acid (ZOL) is a third-generation bisphosphonate, which can inhibit bone destruction in patients with metastatic bone tumors (11)(12)(13) or multiple myeloma. (14) Moreover, ZOL has been shown to exert an antitumor effect against osteosarcoma cells. (15)(16)(17) When ZOL was combined with chemotherapeutic agents, combination therapy showed a synergistic antitumor effect against osteosarcoma and prostate cancer cells.…”
mentioning
confidence: 99%
“…The use of bisphosphonates has been shown to increase the length of time between diagnosis of metastatic disease and first occurrence of a skeletal-related event in patients with multiple myeloma, metastatic breast cancer, metastatic lung cancer, metastatic prostate cancer, and metastatic kidney cancer. 16,[19][20][21][22] Two of these studies also showed clinically significant reduction in perceived bone pain by patients with multiple myeloma and metastatic breast cancer with such treatment. 19,20 For patients presenting with impending or completed pathologic fracture not already taking bisphosphonates, consultation with their medical oncologist regarding initiation of bisphosphonate therapy may be necessary.…”
Section: Perioperative Adjuncts To Treatment Bisphosphonatesmentioning
confidence: 99%